Emotional Stimulation through Animated Student Songs for the Pandemic Covid-19 in Basic Education - Indra Yeni; Desyandri Desyandri; Vivi Anggraini (STAI Hubbulwathan Duri, 2022)
Covid 19 is a virus that attacks the respiratory tract and causes people to limit activities such as schools. it certainly has an impact on children's emotional abilities, they only interact with family, mother, father, etc. Based on field observations that occurred in primary education, there are low emotional abilities of students, it can be seen: 1) that they are often easily offended and cannot control their emotions. 2) they have not been able to express emotions according to the situation, 3) the child has not shown empathy and sympathy. 4) children have not been able to control themselves when they are angry. The research design was carried out for two consecutive years. This research is in the form of research and development using the ADDIE model with the stages of Analysis, Design, Development, Implementation, and Evaluation. Based on research data from the use of animation media. The results showed the emotional development of children. Emotional abilities can be developed through animation media in students' songs. The use of animation media in songs can attract children's interest to use their imagination so that they can express their ideas. Animated song media is a fun activity for students.